Redes sociales y hábitos de lectura en los jóvenes del Sector Junquillo del cantón Vinces año 2021 - Tómala Suarez, Danny Josué (2022)
Social networks and reading habits have produced changes in recent years, it has generated a better ease of relating and communicating, at present, current research is based on the lack that young people in the Junquillo sector have insufficiencies in the area of social networks and reading habits, which causes great difficulty in both communication and knowledge, for this reason the Technical University of Babahoyo allowed me to carry out this study topic which will allow me to know and measure the level of knowledge of social networks and reading habits in the young people of the sector, the study of this theme was supported by bibliographic and historical documentation. The methodology is based as the main method that was quantitatively with the survey method that were represented in a tabular, graphic and textual way of each of the questions attached to the questionnaire, the results of the investigation are presented, the reading habits, in this way, obtaining the results, the problem of the subject was evidenced in a negative way about their reading practices and reading habits.These results allowed the fulfillment of the objective to be justified, which is "Determine the social networks and reading habits in the Junquillo sector in the year 2021", to strengthen the reading habits and social networks, to the young people of the sector, achieving a better development of skills that facilitate critical, analytical and creative thinking.